2018
DOI: 10.3389/fnins.2018.00454
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification and Characterization of the Diuretic Hormone 31 (DH31) Signaling System in the Green Shore Crab, Carcinus maenas

Abstract: The functional characterization of crustacean neuropeptides and their cognate receptors has not kept pace with the recent advances in sequence determination and, therefore, our understanding of the physiological roles of neuropeptides in this important arthropod sub-phylum is rather limited. We identified a candidate receptor-ligand pairing for diuretic hormone 31 (DH31) in a neural transcriptome of the crab, Carcinus maenas. In insects, DH31 plays species -specific but central roles in many facets of physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…CRF is structurally related to mammalian corticotropin, and is called Drome-DH31 in D. melanogaster [136]. DH31 was recently identified in several tissues of the green shore crab C. maenas and its function in rhythmic coordination was established [137]. CT peptide is structurally related to mammalian calcitonin-like peptide and is called Drome-DH44 in D. melanogaster [138].…”
Section: Resultsmentioning
confidence: 99%
“…CRF is structurally related to mammalian corticotropin, and is called Drome-DH31 in D. melanogaster [136]. DH31 was recently identified in several tissues of the green shore crab C. maenas and its function in rhythmic coordination was established [137]. CT peptide is structurally related to mammalian calcitonin-like peptide and is called Drome-DH44 in D. melanogaster [138].…”
Section: Resultsmentioning
confidence: 99%
“…The arrangement of the oyster CTPs with two mature peptides is particularly intriguing as deuterostome CT-type peptide precursors contain either a single peptide (Muff et al, 1995;Sekiguchi et al, 2009) or two peptides, as observed in echinoderm CT-type precursors (Rowe et al, 2014;Suwansa-ard et al, 2018;Zandawala et al, 2017). In the protostomes, the annelid P. dumerilii CT and DH31 precursors (Conzelmann et al, 2013) and the DH31 and CT-A precursors in arthropods (Alexander et al, 2018;Christie, 2008;Christie et al, 2010;Coast et al, 2001;Gard et al, 2009;Li et al, 2007;Veenstra, 2014 comprise only one peptide. In molluscs, this tandem peptide arrangement is observed in bivalves (Zhang et al, 2018) and also in gastropods (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs are characterized by seven transmembrane domains, an external N-terminal domain, and a C-terminal cytosolic domain (25). These are divided among three large classes: rhodopsin-like (Class A), which represents the largest number of GPCRs; secretinlike (Class B); and metabotropic glutamate (Class C) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: G Protein-coupled Receptor-mediated Signalingmentioning
confidence: 99%